Prawnopolityczny wymiar europejskiej tożsamości - Jedlecka, Wioletta (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
This article addresses the crucial question of European identity. The problem how to build European identity not thwarting national identities of Europe is one of the most important challenges of the EU as well as complex theoretical problems.The best way of uniting European nations is to try to build natural bonds between Europeans using the method of small steps. In this way obstacles to free communication of European nations are removed and solidarity bonds are reinforced.In my opinion, in the future, these bonds can make Europeans become something more than a community of passports, the flag and the anthem.
Keywords: europejska tożsamość; Traktat z Lizbony; prawnopolityczny wymiar